Erythropoietin is involved in hemoprotein syntheses in developing human decidua. (11th March 2013) - Shiota, Mitsuru; Yasuda, Yoshiko; Shimaoka, Masao; Tsuritani, Mitsuhiro; Koike, Eiji; Oiki, Masaaki; Matsubara, Junko; Taketani, Shigeru; Murakami, Hitoshi; Yamasaki, Harufumi; Okumoto, Katsumi; Hoshiai, Hiroshi
Abstract Before establishment of feto‐placental circulation, decidua can synthesize hemoproteins to maintain oxygen homeostasis in situ. Using the human decidua of induced abortions ranging from 5 to 8 weeks of gestation, we determined the expression levels of erythropoietin, erythropoietin receptor, cytoglobin, myoglobin, embryonic‐, fetal‐ and adult hemoglobin mRNA by quantitative RT‐PCR analysis and identified their proteins by Western blot and immunohistochemical analyses. Erythropoietin signaling was demonstrated in phosphatidylinositol‐3‐kinase/protein kinase B pathway by Western blot, and the transcriptional factors for erythroid and non‐erythroid heme synthesis were examined by RT‐PCR analysis. In decidua, erythropoietin and its receptor mRNAs, erythropoietin receptor protein and phosphatidylinositol‐3‐kinase, were expressed with a peak at 6 weeks of gestation. Moreover, the decidua during 5 to 8 weeks of gestation expressed embryonic, fetal and adult hemoglobins additionally cytoglobin and myoglobin at transcriptional and protein levels. The heme portion of these hemoproteins is considered to be synthesized by non‐erythroid δ‐aminolevulinate synthase. These hemoproteins were discernible especially in decidual cells concomitant with cytotrophoblast cells and macrophage in these developing decidua. Considering the different capacity for oxygen binding and dissociation among hemoglobins with the oxygen storage capacity for cytoglobin and myoglobin, these hemoproteins appear to play a role in oxygen demand in decidua in situ before development of feto‐placental circulation under the control of erythropoietin signaling.